On fluctuations of the Black Sea basin after the Last Glacial Maximum and Early Holocene - Slavova, K. (Геология и полезные ископаемые Мирового океана, 2009)
The aim of this paper is to determine the causality between the cycles of
Solar Luminosity on the one hand, and the palaeoclimatic data for the Black
Sea region and the fluctuations of the Black Sea Basin on the other hand. The
established cycles of Solar Luminosity can explain the short periodicity
fluctuation of the Black Sea level. It is considered, that the regression of the
Black Sea Basin to the depth of –90…–100 m below the contemporary sea level
during the Early Holocene is not abrupt event. Метою дослідження є встановлення причинно наслідкового зв’язку сонячної
світності з палеокліматичними даними та коливанням рівня Чорноморського басейну. Цикли сонячної активності пов’язані зі зміною палеокліматичної обстановки регіону та могли подіяти на дрібноперіодні варіації чорноморського рівня. Доведено, що
регресія Чорноморського басейну до рівня –90...–100 м за раннього голоцену не є раптовою подією. Цель настоящего исследования – установление причинно следственной связи солнечной светимости с палеоклиматическими данными и колебаниями уровня Чернобассейна. Циклы солнечной активности связаны с изменением палеоклиматической обстановки региона и могли быть индикатором мелкопериодных вариаций
черноморского уровня. Доказано, что регрессия Черноморского басейна до уровня –90...
–100 м в раннем голоцене не является внезапным событием.